Social interaction of coaches and parents increases the motivation of adolescent swimming athletes - Aliya, Rusyda Nur; Nurjaya, Dede Rohmat; Kardjono, Kardjono; Komarudin, Komarudin; Novian, Geraldi (Universitas Tanjungpura, 2025)
Background. The reason for this study is the mismatch between theory and reality in the field, where social support from parents and coaches which should tend to be positive in increasing athlete motivation, in practice can actually become pressure and cause stress and loss of motivation. Objectives. This research addresses the understanding of how social interactions between coaches and parents influence the motivation of adolescent swimming athletes. The purpose of this study, to determine the effect of social interactions of coaches and parents on the motivation of adolescent swimming athletes. Methods. The method used in this research is descriptive method with quantitative approach. The population used was Samudra Swimming Club swimming athletes, the sample of athletes taken was 30 athletes according to the Age Category (KU) of adolescents 10-17 years taken through purposive sampling. This study used an instrument in the form of a questionnaire